ANALYSIS OF MORAL VALUES IN THE NOVEL 'PUDARNYA PESONA CLEOPATRA' BY HABIBURRAHMAN EL-SHIRAZY AND ITS APPLICATION AS TEACHING MATERIAL FOR ANALYZING THE CONTENT AND LANGUAGE OF THE NOVEL FOR 12TH-GRADE HIGH SCHOOL STUDENTS - Wahyuni, Siti Sri; Subaweh, Ahmad Maskur; Naufal, Muji Zain (Transpublika Publisher, 2023)
The advancement of globalization in today's society has had a negative impact on the manners and ethics of students. As a result, education plays a crucial role in shaping the character of students, particularly in terms of moral values. This study aims to examine the moral values depicted in the novel